Fueling Open‐Source Drug Discovery: 177 Small‐Molecule Leads against Tuberculosis. Issue 2 (10th January 2013) - Ballell, Lluís; Bates, Robert H.; Young, Rob J.; Alvarez‐Gomez, Daniel; Alvarez‐Ruiz, Emilio; Barroso, Vanessa; Blanco, Delia; Crespo, Benigno; Escribano, Jaime; González, Rubén; Lozano, Sonia; Huss, Sophie; et al.
Abstract With the aim of fuelling open‐source, translational, early‐stage drug discovery activities, the results of the recently completed antimycobacterial phenotypic screening campaign against Mycobacterium bovis BCG with hit confirmation in M. tuberculosis H37Rv were made publicly accessible. A set of 177 potent non‐cytotoxic H37Rv hits was identified and will be made available to maximize the potential impact of the compounds toward a chemical genetics/proteomics exercise, while at the same time providing a plethora of potential starting points for new synthetic lead‐generation activities. Two additional drug‐discovery‐relevant datasets are included: a) a drug‐like property analysis reflecting the latest lead‐like guidelines and b) an early lead‐generation package of the most promising hits within the clusters identified.